Ethics and architecture: the case of Albert Speer - Lillegard, Norman (Journal of Architecture and Urbanism, 2014)
It has been argued that there are obligations, or virtues and vices, that pertain uniquely to architectural practice. Thus Jack Sammons has argued that the moral failings of the Nazi architect Albert Speer were failings specific to him as an architect (qua architect). I argue that Sammons’ account misappropriates ideas about the virtues from Alasdair MacIntyre and for that and other reasons does not succeed. Nonetheless it may be possible to support the idea that there can be a specifically architectural ethics. I comment briefly on Heidegger’s notion of ‘dwelling’ in trying to indicate what might be involved in such an ethics.